KARAKTERISTIK PERUSAHAAN, KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN DAN KEMUNGKINAN KECURANGAN PELAPORAN KEUANGAN - Husaini Husaini; Salma Yuniza (Jurnal Akuntansi dan Keuangan, 2020)
This research aims to obtain empirical evidence regarding the effect of the characteristics of the company's financial disclosure statements of completeness and consequently to the financial statement fraud. Characteristics of companies in this study consists of company size, leverage, liquidity, the company's corporate status and age.The population in this research is the manufacturing companies listed on the Indonesia stock exchange over the years 2011-2013. Purposive sampling method based on retrieved 98 companies listed on the Indonesia stock exchange as research samples. Research on regression model using two. Using multiple linear regression, the study found the size of the company and the company's status affect the completeness of the disclosure of the financial statements. Leverage, liquidity and the age of the company does not affect the completeness of the disclosure of the financial statements. Then, the sample is categorized into 2 categories by using the Beneish model M-Score that the company that did the possibility of fraudulent financial reporting and company didn't do the possibility of fraudulent financial reporting. Using the method of logistic regression, this research found that the completeness of the pengungakap financial statements have no effect against the possibility of fraud in financial reporting.